Revolutionizing Ethnographic Collection Introduction through Augmented Reality Technology in Museum - Mewengkang, Alfrina; Sumual, Herry; Teruna, Ilyas (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
The North Sulawesi Provincial State Museum is one of the tourist destinations that offers a profound experience in exploring the historical, cultural, and tourism heritage of Indonesia. Visitors can learn about various valuable historical collections, including ethnographic collections, which hold significant historical value. However, the information provided about the ethnographic collection is very limited, making it challenging for visitors to understand and appreciate it. This research aims to develop an application for recognizing the museum's ethnographic collection using Augmented Reality (AR) technology, which will make it easier for visitors to obtain information about the collection. This application was designed and developed using the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: conceptualization, design, material gathering, assembly, testing, and distribution. The result of this research is an Android-based AR Museum application that can display information about the ethnographic collection in the form of text, sound, and 3D images. This application can enhance the visitor experience, especially in understanding and appreciating the cultural heritage and traditions represented in the ethnographic collection of the North Sulawesi Provincial State Museum. Additionally, this application can improve the accessibility of information about the ethnographic collection and promote the museum as a center for heritage preservation, education, and culture.